Fenomena Karoshi dan Karojisatsu dalam Animasi Zom 100: Bucket List of the Dead - Ikhsan, Juniardi; Syihabuddin (Jurnal Bahasa Jepang Taiyou, 2023)
The phenomenon of karoshi (overtime at work) or karojisatsu (suicide due to overtime) is a phenomenon that is still unfamiliar to Indonesians. Karoshi is an event that is still a serious problem for the Japanese government. Many people die from karoshi or karojisatsu because of the actions of black companies (ブラック企業・burakku kigyou) in Japan who always pressure their employees to work harder and overtime irregularly so that it has a negative impact on the lives of Japanese people. The purpose of this research is to find out what processes and symptoms or stages precede the occurrence of karoshi or karojisatsu seen from the perspective of the main character of the animation named Akira Tendo. However, he is lucky to be alive and can avoid karoshi or karojisatsu. Because, the world was suddenly attacked by zombies and suddenly he was free from the pressure of the company all this time. From the results of the study, by taking a phenomenological approach, the author can conclude that there are 3 symptoms or stages leading to a person becoming a victim of karoshi due to overtime work, namely: (1) The first stage is the symptom of depression (憂鬱・yuuutsu). (2) The second stage is symptoms of stress (ストレス・sutoresu).  (3) The third stage is depression (うつ病・utsubyou).